Inovasi Sistem Terpadu Pelayanan Geriatri dalam Meningkatkan Kualitas Hidup Lansia di RSUD Grati Kabupaten Pasuruan - Kuwes Al Koroni; Hayat; Langgeng Rachmatullah Putra (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
A type of administration used by service providers to deliver a service that can satisfy the needs of service users is known as public service. The government offers a number of services, including health care, to uphold the welfare of the people. The purpose of this study is to identify, characterize, and evaluate the SISTER PERI SI-PLUS innovation in enhancing the elderly population's quality of life at Grati Regional Hospital in Pasuruan Regency. Additionally, the study aims to identify the factors that promote and hinder the implementation of the SISTER PERI SI-PLUS innovation in enhancing the elderly population's quality of life at Grati Regional Hospital in Pasuruan Regency. Qualitative research approaches are used in the study. Techniques for gathering data include documentation, observation, and interviews. Researchers evaluated five factors—Program Understanding, Target Accuracy, Timeliness, Goal Achievement, and Real Change—to evaluate the SISTER PERI SI-PLUS innovation's implementation. The findings of this study demonstrate that the SISTER PERI SI-PLUS innovation has not been deemed effective in enhancing the quality of life of the elderly at Grati Hospital, Pasuruan Regency. This is due in part to the fact that not all elderly people comprehend the SISTER PERI SI-PLUS innovation, and in part to the fact that not all elderly people receive the health services provided by this SISTER PERI SI-PLUS innovation. The elderly population's lack of health awareness is the main obstacle to the SISTER PERI SI-PLUS innovation.